2013
DOI: 10.1002/emmm.201302475
|View full text |Cite
|
Sign up to set email alerts
|

Caudo‐rostral brain spreading of α‐synuclein through vagal connections

Abstract: α-Synuclein accumulation and pathology in Parkinson's disease typically display a caudo-rostral pattern of progression, involving neuronal nuclei in the medulla oblongata at the earliest stages. In this study, selective expression and accumulation of human α-synuclein within medullary neurons was achieved via retrograde transport of adeno-associated viral vectors unilaterally injected into the vagus nerve in the rat neck. The exogenous protein progressively spread toward more rostral brain regions where it cou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

16
229
0
4

Year Published

2014
2014
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 242 publications
(249 citation statements)
references
References 23 publications
16
229
0
4
Order By: Relevance
“…Similar phenomena are observed not only for monomeric α-synuclein, but also for oligomeric and fibrillar α-synuclein, the latter most likely being a significant contributor to the Lewy pathology propagation in PD conditions. The vagal route of α-synuclein transport has also been documented by systemic administration of the environmental toxin rotenone [36], as well as by directly injecting adeno-associated viral vectors overexpressing human α-synuclein into the vagal nerve [49]. The clear difference between the present study and previous work is that exogenous α-synuclein forms are not readily detected in the vagal nerves/neurons and the brain parenchyma [15,31,32,49].…”
Section: Discussionmentioning
confidence: 68%
“…Similar phenomena are observed not only for monomeric α-synuclein, but also for oligomeric and fibrillar α-synuclein, the latter most likely being a significant contributor to the Lewy pathology propagation in PD conditions. The vagal route of α-synuclein transport has also been documented by systemic administration of the environmental toxin rotenone [36], as well as by directly injecting adeno-associated viral vectors overexpressing human α-synuclein into the vagal nerve [49]. The clear difference between the present study and previous work is that exogenous α-synuclein forms are not readily detected in the vagal nerves/neurons and the brain parenchyma [15,31,32,49].…”
Section: Discussionmentioning
confidence: 68%
“…Numerous in vitro and in vivo studies showed that α-synuclein can be released from one cell, taken up by another, and seed aggregation of endogenous α-synuclein in the recipient cell, with resulting deleterious pathological changes [129,[241][242][243][244][245][246]. It is likely that this transmission can occur without cell death or membrane leakage of the donor cell, perhaps through exocytosis [247], although cell death and membrane degeneration would accelerate the transmission by releasing a large amount of α-synuclein aggregates.…”
Section: α-Synuclein "Strains" and Prion-like Transmissionmentioning
confidence: 92%
“…exposure to the environmental toxin rotenone (22) as well as following direct injection of adenoassociated viral vectors overexpressing human α-synuclein into the vagus nerve (23). A route from intrinsic enteric neurons to the vagus nerve is supported by the observation that both myenteric neurons and preganglionic vagal nerves express α-synuclein (24).…”
Section: Introductionmentioning
confidence: 99%